Jejak Historis Al-Irsyad Al-Islamiyah dan Kiprahnya dalam Pengembangan Pendidikan Islam - Anshari, Zainal; Fahruddin, Ahmad Hanif (Universitas Islam Lamongan, 2020)
Indonesia is a country with the largest Muslim population in the world. As the majority religion, of course Islam becomes a religion that has a wealth of internal dynamics, both in the context of Islam itself and in the context of Indonesia. This paper discussed that Islam in Indonesia has long-standing organizations. The existence of Islamic organizations even existed though Indonesia had not yet been independent. In this research, the writers conducted a typology of Islamic organizations standing before and after independence including their respective movement orientation. Of the many Islamic organizations considered quite old, the al-Irsyad is one of the Islamic organizations contributing to its historical footprint. Various figures of independence, national figures and even among the scholars were born from the womb of this organization. With a relatively large number of followers, this mass organization oversees educational institutions ranging from elementary to upper secondary levels, which have to this day still existed and continued to reproduce the nation's cadres.